2011
DOI: 10.1161/circulationaha.110.988436
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomographic Analysis of In-Stent Neoatherosclerosis After Drug–Eluting Stent Implantation

Abstract: Background-We report findings from optical coherence tomography (OCT) of in-stent neoatherosclerosis as a cause of drug-eluting stent (DES) failure. Methods and Results-Optical 024).Compared with DES Ͻ20 months after implantation (the best cut-off to predict TCFA-containing neointima), DES Ն20 months after implantation had a higher incidence of TCFA-containing neointima (69% versus 33%, Pϭ0.012) and red thrombi (27% versus 0%, Pϭ0.007). Patients with unstable (versus stable) angina had an increasing number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
237
4
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 336 publications
(256 citation statements)
references
References 39 publications
12
237
4
3
Order By: Relevance
“…These results will help us better understand the cellular and molecular basis of disease progression via longitudinal studies. OCT has been recently used in conjunction with imaging techniques such as scanning laser ophthalmoscopy, [32][33][34] fundus autofluorescence, 35 fluorescein angiography, 32,36,37 ultrasound, 38 and Indocyanine Green angiography, 39 helping in better diagnosis of diseased tissue. Multiphoton imaging has also been used to study fluorescent cells in the mouse retina.…”
Section: Discussionmentioning
confidence: 99%
“…These results will help us better understand the cellular and molecular basis of disease progression via longitudinal studies. OCT has been recently used in conjunction with imaging techniques such as scanning laser ophthalmoscopy, [32][33][34] fundus autofluorescence, 35 fluorescein angiography, 32,36,37 ultrasound, 38 and Indocyanine Green angiography, 39 helping in better diagnosis of diseased tissue. Multiphoton imaging has also been used to study fluorescent cells in the mouse retina.…”
Section: Discussionmentioning
confidence: 99%
“…4,5) Results of five-year follow up from SIRIUS, j-Cypher Registry have shown that very late stent thrombosis and late target lesion revascularization are continuous hazards, lasting at least up to five years after implantation of sirolimus-eluting stents 19,20) . Recent reports have suggested NA as a possible pathway for late stent failure, in which NA was defined as lipid laden plaque or calcification inside the stent, and these atherosclerotic plaques often includes vulnerable characteristics such as TCFA, intimal rupture, and thrombus 7,8) . This recent knowledge of outcomes after stent implantation can be attributed to the introduction and progression of intracoronary imaging technology such as OCT.…”
Section: Discussionmentioning
confidence: 99%
“…6,7) The development of optical coherence tomography (OCT) has enabled us to identify in-stent NA, which is characterized by vulnerable plaque features such as lipid laden plaque, thin-cap fibroatheromas (TCFA), and luminal thrombus and therefore, patients with NA have often unstable coronary disease. 8) Previous reports have suggested that elapsed time after stent implantation, smoking, and chronic kidney disease (CKD) are predictors of NA after stent implanatation, [9][10][11] however, the precise mechanism of NA has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…39 Kang et al also demonstrated that DES >20 months in comparison with DES <20 months after implantation had a higher incidence of TCFA-containing neointima (P=0.012). 40 With both DES and BMS, neoatherosclerosis might be an important mechanism of very late stent failure, including thrombosis and restenosis ( Figure 6). …”
Section: Neoatherosclerosismentioning
confidence: 99%